A Taxonomy of Blockchain Consensus Methods - Jeff Nijsse; Alan Litchfield (Cryptography, 2020)
For a blockchain, consensus is the foundation protocol that enables cryptocurrencies such as Bitcoin to maintain state. Additionally, to ensure safety and liveness for a publicly accessible and verifiable ledger, fault tolerance must be robust. However, there appears to be a degree of misunderstanding about how consensus is applied across blockchains. To assist researchers considering variations between them, this study presents a rational classification of consensus methods applied to current blockchains. The study provides a survey of 19 methods classified by the scarce resource they employ: clock-cycles, bits, tokens, votes, time, and biometrics. Blockchain implementations are split between consensus algorithms requiring proof of resource and those that use majority voting to update the ledger.